Kilka uwag o realizacji przepisów ochrony zabytków. Problemy praktyczne - Sabaciński, Marcin (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article focuses on a few problematic aspects related the enforcement of the heritage conservation law, with a particular emphasis on the register of objects of historic significance. A provincial register of such objects forms the basis for a given object to be covered by statutory forms of protection, and the very inclusion of a property into the register causes specific legal effects for the owner, user or potential investors. At the same time there is no obligation to inform such individuals of the property being included in the cultural heritage register, and the existing methods for disclosing that fact are far from effective. Further paragraphs of the article elaborate on the inability to complete a national register of archaeological heritage using the existing research methodology and the issue of insufficient legal mandate for keeping the register of objects located in marine areas. Finally, the author indicates the problem of conservation control which, considering the time regime provided for by the Code of Administrative Procedure, is ineffective by nature in the cases of sudden threat to the protected objects.
Keywords: ochrona zabytków; realizacja przepisów ochrony zabytków